A novel compressive stress-based osteoarthritis-like chondrocyte system. Issue 10 (May 2017) - Young, In-Chi; Chuang, Sung-Ting; Gefen, Amit; Kuo, Wei-Ting; Yang, Chun-Ting; Hsu, Chia-Hsien; Lin, Feng-Huei
Mechanical stress damage and insufficient self-repair can contribute to osteoarthritis (OA) in the affected joint. As the effects of stress on chondrocyte metabolism can regulate cartilage homeostasis, the specific stress–response condition is therefore a key to the generation of an OA disease model. We aimed to produce a specific stress- and cell-based OA model after evaluating the metabolic responses of chondrocytes in response to a series of static and cyclic compression stressors. A static load exceeding 40 psi initiated extracellular matrix (ECM) degradation through a decrease in the sulphated-glycosaminoglycan (GAG) content, upregulation of catabolic matrix metalloproteinase (MMP)-13 encoding gene expression, and downregulation of the ECM-related aggrecan and type II collagen encoding genes within 24 h. Indicators of pro-inflammatory events and oxidative stress were found to correlate with increased IL-6 expression and reactive oxygen species (ROS) production, respectively. However, chondrocytes stimulated by moderate cyclic loading (30–40 psi) exhibited increased ECM-related gene expression without significant changes in catabolic and pro-inflammatory gene expression. BMP-7 expression increased at cyclic loading levels above 30–60 psi. These results demonstrated that static compression exceeding 60 psi is sufficient to produce OA-like chondrocytes that exhibit signs of ECM degradation and inflammation. These OA-like chondrocytes could therefore be used as a novel cell-based drug screening system. Impact statement: The lack of an effective treatment for osteoarthritis (OA) reflects the great need for alternative therapies and drug discovery. Disease models can be used for early-stage compound screening and disease studies. Chondrocytes are solely responsible for the maintenance of the articular cartilage extracellular matrix. Our strategy involved the generation of a cell-based model of OA, a more readily studied disease. Instead of using animal cartilage explants, we incorporated isolated porcine chondrocytes with hydrogel to form three-dimensional assemblies. We could identify the specific magnitude-dependent metabolic responses of chondrocytes by applying a series of static and cyclic compression, and therefore successfully generated a novel OA-like cell-based model for drug screening.